Present Status and Prospects of Organic Farming in Ramanathapuram District - M. Manikandan; A. S. Arachana; L. Mohammad Ghouse, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
The impact of technology and interference in natural ecosystems often comes with side effects. Over the past fifty years, the widespread use of pesticides and herbicides to boost crop yields has led to a growing interest in alternative, chemical-free farming methods like organic farming. Organic farming not only aligns with natural processes but also provides the opportunity to command premium prices, particularly in markets such as Tamil Nadu. Given that organic farming requires fewer prerequisites compared to conventional chemical-based methods, there is an increasing demand for organic products both domestically and internationally. Consumers are willing to pay more for assurance that their food is produced through natural systems, highlighting the need for robust certification processes in the country. The potential for organic food industries to expand and contribute to the Indian economy is significant. Agriculture, with a rich and enduring history, is celebrated as a noble profession by Thiruvalluvar, who said, “They live, who plough for life; all others workship in the rear.” Organic farming presents a viable alternative to conventional high-input practices that rely on synthetic fertilizers, fungicides, and pesticides. It focuses on the principle that soil is a living system, thus excluding synthetic products and relying instead on crop rotation, animal manures, crop residues, green manures, and biological pest control to maintain soil health and productivity. Organic crops often fetch higher market values, and their production is on the rise. Advanced markets heavily regulate the sale of organic products, ensuring their authenticity. Organic farming, with its low environmental impact, offers a way to rehabilitate and enhance degraded agricultural land. It represents one of several innovative farming systems poised to contribute significantly to future global food and ecosystem security.